Fractographic analysis of lithium silicate crown failures during sintering - Lohbauer, Ulrich; Wendler, Michael; Rapp, Doreen; Belli, Renan (SAGE Open Medical Case Reports, 2019)
The two-step production process of glass-ceramic dental restorations involves a computer-aided design/computer-aided machining step followed by a crystallization firing for the final material properties to be achieved. Certain firing parameters are believed to trigger spontaneous fracture of crowns during the cooling process. In this study, cooling fractures have been reproducibly observed and investigated using fractography combined with material (glass transition temperature) and process (cooling rate) characterization. Stress distribution was visualized using birefringence measurements. Fractographic observations revealed fracture starting at the intaglio side of the crowns specifically at contact points with the support firing pins. Further analysis showed that a fast cooling rate was applied during the glass transition region. Thermal stresses were concentrated around the firing pin supports and released the fracture. To prevent such fractures, a slow cooling protocol below the glass transition temperature is our recommendation to dental technicians. Furthermore, the use of planar firing pad or paste supports is advised over the use of point contact supports.
CRIS-Team WoS Importer:2019-04-04